Local Level Monitoring Systems in Community Forestry: Challenges, Opportunities and Directions for Future (Journal of Forest and Livelihood, 2024)
A recent study has demonstrated that local level monitoring systems, that could encourage learning and adaptiveness in forest management, are poorly developed, and that this presents a constraint to equitable and active management of forests. This paper reviews the contextual factors and emerging concepts of monitoring, and identifies gaps and prospects. Based on lessons gained thus far, strategies for facilitating local level monitoring are also explored.